Pharmacokinetics Study of Herb–Drug Interaction of Berberine and Glipizide in Beagle Dogs Using UPLC-MS/MS - He Qi; Wenjiong Wang; Xianghan Zhang; Bingyang Shang (International Journal of Analytical Chemistry)
Based on the establishment and validation of a UPLC-MS/MS method for detecting glipizide in beagle plasma, the herb–drug interaction (HDI) between berberine and glipizide was studied. After gradient elution separation of glipizide and internal standard, multiple reaction monitoring was used for detection in positive ion mode. The ion reactions used for quantitative analysis were glipizide m/z 446.0 ⟶ 321.0 and IS m/z 307.1 ⟶ 220.0. Six beagle dogs were treated with glipizide alone and berberine intervention, and the pharmacokinetic changes of glipizide were compared. The UPLC-MS/MS method has good linearity and the advantages of being green, simple, sensitive, and fast. After continuous administration of berberine to beagle dogs for 7 days, the pharmacokinetic process of glipizide changed with Cmax, AUC(0-t) and AUC(0-∞) increasing, t1/2 prolonging, and CL and Vd decreasing. When using combination therapy, attention should be paid to possible HDI.